Deux piliers de l’économie grecque d’aujourd’hui - Joëlle Dalègre (Cahiers Balkaniques)
While Greece is sinking in a bottomless economical and financial crisis, her merchant navy is the first in the world and the tourist activity reaches a peak in 2015. Nevertheless the shipowners don’t contribute, it is said, to the national budget according to their means, while threatening to leave the country of their privileges are affected… and the tourism while offering many opportunities for VAT evasion, complains about the new VAT record increase… This communication means just to review the main points about these situations.